Избранные произведения: авторизованный перевод с грузинского / Л. Киачели ; [послесловие Б. Жгенти] - Киачели Лео (Заря Востока, 1955)
Экземпляры: КХ (20190206) / Инвентарный номер: 197654 / Сис.шифр: С / Авт.знак: К 38 / ГРНТИ: 17 / ББК: 84(4/8)